PERFORMANCE EVALUATION OF ETHERNET TRANSMISSION USING M-ARY PULSE AMPLITUDE MODULATION TECHNIQUES - APENA WALIU OLALEKAN; OLASUNKANMI OMOWUMI GRACE; SALAKO ANUOLUWAPO (Journal of Engineering Studies and Research)
Low installation costs and high data rates reaching up to 10 Gbps, characterized Ethernet as the local area network (LAN) technology of choice to satisfy the increasing need for high-speed data transmission in packet-based networks. As demand for high speeds in data has increased, copper Ethernet has been integrated to handle these higher speeds. The IEEE 802.3ae* 2002 (10 Gigabit Ethernet) standard is based on data transmission over optical fibre only and in full-duplex mode. This study considered performance evaluation of Pulse Amplitude Modulation (PAM) and multilevel (PAM-16) technology in comparison with other PAM versions was carried out to investigate copper Ethernet with respect to higher speed characteristic and error performance. The evaluation was carried out in MATLAB R2017b simulation environment; this provides calculated bit error rates (BER) of the considered modulation schemes under different channel conditions. The results show that PAM-16 has a BER of .which is significantly lower than that of PAM-2 and PAM-4. Additionally, Hamming code were used to detect and correct errors that are inherent in the design and the efficiency of each level of PAM used was analyzed.